The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1186/s12935-021-01835-w
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA-SNHG6 promotes the progression of hepatocellular carcinoma by targeting miR-6509-5p and HIF1A

Abstract: Background Accumulating evidences have been reported that long noncoding RNAs play crucial roles in the progression of hepatocellular carcinoma (HCC). SnoRNA host gene 6 (SNHG6) is believed to be involved in several human cancers, but the specific molecular mechanism of SNHG6 in HCC is not well studied. Methods In this study, we experimentally down-regulated the SNHG6 in two hepatocellular carcinoma cell lines in vitro, and then measured the prolif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…LncRNA can mechanically act as a competing endogenous RNA (ceRNA) and bind with miRNAs to inhibit the effect of miRNA on their target mRNAs. SNHG6 promotes G1/S-phase transition in HCC by impairing miR-204-5p-mediated inhibition of E2F1 (Chen et al 2021 ) and promotes the progression of HCC by targeting miR-6509-5p and HIF1A (Fan et al 2021 ). In addition to combining with miRNAs, lncRNA has also been reported to be able to bind to proteins and affect their function.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA can mechanically act as a competing endogenous RNA (ceRNA) and bind with miRNAs to inhibit the effect of miRNA on their target mRNAs. SNHG6 promotes G1/S-phase transition in HCC by impairing miR-204-5p-mediated inhibition of E2F1 (Chen et al 2021 ) and promotes the progression of HCC by targeting miR-6509-5p and HIF1A (Fan et al 2021 ). In addition to combining with miRNAs, lncRNA has also been reported to be able to bind to proteins and affect their function.…”
Section: Discussionmentioning
confidence: 99%
“…In the past 10 years, lncRNA has become a topic of intense interest in cancer research. LncRNAs play important roles in HCC by regulating cell proliferation, migration, and invasion [23][24][25]. The lncRNA LIMT has been identified as a novel and critical regulator in breast cancer [17].…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that cancer progression is fostered by SNHG6 [ 170 , 171 , 172 , 173 ]. Moreover, SNHG6 can elevate the expression of HIF-1α by either sponging miRNAs or enhancing the translation of HIF-1α mRNA [ 150 , 151 , 152 ].…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%
“…As a consequence, SNHG6 enhances migration and invasion abilities of hepatocellular carcinoma cells, along with an increase in HIF-1α expression. In xenografts, the growth of hepatocellular carcinoma is suppressed by the downregulation of SNHG6 [ 151 ] ( Figure 2 and Table 2 ).…”
Section: Lncrnas Regulating Hif-1α Expressionmentioning
confidence: 99%